Roles of long non-coding RNA HULC in human digestive system cancers - Huang, Liqing (Frontiers in Oncology, 2025)
Digestive system cancers, including hepatocellular carcinoma (HCC), gastric cancer (GC), pancreatic cancer (PC), and colorectal cancer (CRC), pose a significant global health burden with high morbidity and mortality rates. Their tumorigenesis and progression are driven by complex interactions between genetic alterations and environmental factors. In recent years, long non-coding RNAs (lncRNAs) have emerged as critical regulators in cancer initiation, metastasis, and drug resistance through epigenetic modulation, transcriptional regulation, and post-transcriptional modifications. Among them, HULC, a well-characterized oncogenic lncRNA, was initially identified in HCC due to its remarkable upregulation. Subsequent studies have revealed that HULC is aberrantly overexpressed in multiple gastrointestinal malignancies, including GC, PC, and CRC, and its expression levels strongly correlate with advanced clinical stage, metastatic potential, and poor patient prognosis. Mechanistically, HULC exerts its oncogenic effects by interacting with genes, RNA, and proteins to promoting the Warburg effect, and inducing epithelial-mesenchymal transition (EMT), thereby facilitating tumor progression. This review comprehensively summarizes recent advances in understanding the biological roles, molecular mechanisms, and clinical implications of HULC in digestive system cancers. Furthermore, we discuss its potential as a novel diagnostic biomarker and therapeutic target, providing insights into precision medicine strategies for gastrointestinal malignancies.